The whisper - Zagarenski, Pamela (Boston Houghton Mifflin Harcourt, 2015)
Her magical book of stories is wordless until a whisper in the wind tells a little girl to imagine a story for each page.
Booklist starred
Publisher's Weekly
School Library Journal starred
Booklist starred, September 2015
Horn Book, September 2015
Kirkus Starred, August 2015
Keywords: Books and reading -- Juvenile fiction; Imagination -- Juvenile fiction; Magic -- Juvenile fiction; Books and reading -- Fiction; Imagination -- Fiction; Magic -- Fiction; Books and reading -- Fiction; Imagination -- Fiction; Magic -- Fiction; Fantasy fiction